Antibacterial activity of nanocomposites of silver and bacterial or vegetable cellulosic fibers - Pinto, Ricardo J. B. (2009)
Cellulose/Ag nanocomposites were prepared using two distinct methodologies and two cellulose substrates: vegetable and bacterial cellulose. These nanocomposites were characterized in terms of their morphology and chemical composition. Detailed studies on the antibacterial activity of these materials were carried out for Bacillus subtilis, Staphylococcus aureus and Klebsiella pneumoniae. Silver nanoparticles present in the cellulosic fibers in concentrations as low as 5.0 10 4 wt.% make these nanocomposites effective antibacterial materials. We anticipate that the versatile use of these cellulose-based nanocomposites can bring a promising strategy to produce a wide range of interesting materials where antibacterial properties are crucial.